Alleviating psychological distress associated with a positive cervical cancer screening result: a randomized control trial - Yukari Isaka; Ai Hori; Rie Tanaka; Masao Ichikawa (BMC, 2021)
Abstract Background The method of communicating a positive cancer screening result should seek to alleviate psychological distress associated with a positive result. We evaluated whether the provision of information through a leaflet would help reduce psychological distress in a randomized controlled trial. Methods The participants were women aged 20-69 years who were about to undergo cervical cancer screening at health centers. Before the screening, they received hypothetical screening results, with a leaflet (intervention group, n = 493) or without it (control group, n = 479), randomly. Their psychological distress and intention to undergo further examination were then compared between the intervention and control groups. Results After the intervention (providing a leaflet with hypothetical screening results), psychological distress appeared to be higher in the control group than in the intervention group among those who received a hypothetical positive screening result (odds ratio: 2.57, 95% confidence interval: 1.87-3.54), while 95% and 97% of those in the intervention and control groups, respectively, reported that they would undergo further examination. Conclusions Information provision might help reduce psychological distress but not hinder further examination among women who screen positive for cervical cancer. Trial registration: UMIN Clinical Trials Registry UMIN000029894. Date of Registration: November 2017.